IDENTIFICATION OF AQUIFERS BASED ON THE VERTICAL ELECTRICAL SOUNDING (VES) METHOD SCHLUMBERGER CONFIGURATION CASE STUDY: PULAU BAAI KAMPUNG MELAYU SUB-DISTRICT, BENGKULU CITY, INDONESIA - Rafly, Tegar Al; Refrizon, Refrizon; Hadi, Arif Ismul; Ansory, Andre Rahmat Al; Raihana, Hana (Indonesian Physical Review, 2025)
Investigation of the groundwater potential in the Pulau Baai area, Kampung Melayu Sub-district, Bengkulu City, must be carried out in such a way that the activities and needs of the people in the area can be fulfilled and the needs of the population in the area can be met. This study aims to determine the status of groundwater using the Schlumberger configuration geoelectric method. Measurements were made using a resistivity meter, and the results for each configuration depended on changes in resistivity. Measurements for each configuration depend on changes in resistivity at depth, the vertical direction (sounding), and the lateral direction (mapping), so hydrogeological analysis in this activity aims to get the maximum use of groundwater / underground water in aquifers for raw water needs. The dominant rock structures in the study area are clay, alluvium, siltstone, and sandstone, as well as some rocks with suitable porosity and permeability as water carriers, such as sand and gravel. However, what appears to have considerable potential is that groundwater is found at depths of 4-53 meters in VES 1, VES 2, VES 3, VES 5, and VES 10. The results of the analysis show that the location of the Pulau Baai, Kampung Melayu Sub-district, Bengkulu City Priority Utilization Area is within the groundwater storage area, so it can be used to meet the raw water needs of the study area.